PENINGKATAN HASIL TANAMAN OKRA (Abelmoschos esculentus L Moench) DENGAN KOMPOSISI MEDIA TANAM DAN PUPUK CAIR HAYATI - Teguh Riyanto; Muhammad Ihsan; Tri Pamujiasih (Universitas Boyolali, 2020)
This study was conducted to determine the increase of okra (Abelmoschus esculentus L Moench) plants with composition of planting media and biological liquid fertilizer. This research was conducted in December 2018 to March 2019, in Duren Hamlet, Wonorejo Village, Kalijambe District, Sragen Regency at an altitude between 100 m above sea level. This research is a factorial experiment with a completely randomized design (CRD) pattern consisting of two treatment factors. The first treatment factor is the composition of the planting medium (M) which consists of 4 levels (M1 = one soil without manure and husk charcoal = 1: 0: 0, M2 = one soil + one manure + one husk charcoal = 1: 1 : 1, M3 = one hold + two manure + one husk charcoal = 1: 2: 1, M4 = one soil + three manure + one husk charcoal = 1: 3: 1). The second treatment factor, the concentration of biological liquid fertilizer (P) consisting of 4 levels (P1 = 0 ml / l water, P2 = 2 ml / l water, P3 = 3 ml / l water, P4 = 4 ml / l water). Parameters observed included plant height, number of leaves, number of fruits, weight of fruit per plant, weight of fresh stover. The results showed that treatment of composition planting medium (M) had very significant effect on the parameters of plant height, number of leaves, number of fruits, weight of fruit per plant and weight of fresh stover, while the concentration of biological liquid fertilizer (P) was not significantly different and (MxP) gives interactions not significantly different. The results of the average observations of parameters obtained by the best plant height found in M2 planting media with an average height (121.82) cm, the number of leaves is good in M3 (28.46) and M4 planting media (28.13) , the weight of fresh stover was found in M3 (415.04) g and M4 (404.71) g media, the highest number of fruits per plant was found in M3 (16.94) and M2 (16.80), and heavy planting media fruit per best plant in M3 planting media (452.95) g. The results of the study were obtained from the whole treatment of the best compass media on media composition (M3 = one soil + two manure + one rice husk charcoal = 1: 2: 1) which gave the best results on the parameter number of leaves (28.46), number of fruits per plant (16.94), weight of fruit per plant (452.95) gr, heavy berangkasan (415.04) gr. While the lowest results on the planting medium (M1) on the parameters of plant height (63.30) cm, number of leaves (14.42), number of fruits (3.79), weight of fruit per plant (33.57) gr and weight of fresh stover (29.75) gr.